2000
DOI: 10.1054/bjoc.1999.0981
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the PA2G4 (EBP1) protein with ErbB-3 and regulation of this binding by heregulin

Abstract: SummaryThe processes by which ErbB-3, an inactive tyrosine kinase, exerts its biological effects are poorly understood. Using the yeast two-hybrid system, we have isolated an ErbB-3 binding protein (Ebp1) that interacts with the juxtamembrane domain of ErbB-3. This protein is identical to that predicted to be encoded for by the human PA2G4 gene. Ebp1 is the human homologue of a previously identified cell cycleregulated mouse protein p38-2G4. Two transcripts of ebp1 mRNA (1.7 and 2.2 kb) were detected in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
155
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(160 citation statements)
references
References 34 publications
3
155
1
1
Order By: Relevance
“…This extends previous observations made in tumor cell lines Yoo et al, 2000;Xia et al, 2001a), demonstrating that both normal and transformed cells are sensitive to EBP1 over- expression. Most importantly, we observed that the mutant K20A-K22A, which is only cytosolic and not nucleolar, is unable to inhibit proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…This extends previous observations made in tumor cell lines Yoo et al, 2000;Xia et al, 2001a), demonstrating that both normal and transformed cells are sensitive to EBP1 over- expression. Most importantly, we observed that the mutant K20A-K22A, which is only cytosolic and not nucleolar, is unable to inhibit proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…Further study is needed of the involvement of non-NRG, non-ERBB regulators of ERBB3, such as CDK5, [122][123][124] BRK, 125 SRC, 126 and MET. 120 The fascinating and widely expressed ERBB3 effector EBP1 has thus far been examined mainly in mammary and prostate cells; [154][155][156][157][158][159][160][161][162][163][164] may it be important also in other cancers where ERBB3 is clearly a player, such as lung and melanoma? It is hoped that full understanding of the regulation and functions of ERBB3 will facilitate its integration into cancer management.…”
Section: Discussionmentioning
confidence: 99%
“…154 EBP1 is encoded by human gene PA2G4 (human homolog of the mouse p38-2G4 protein, a cell cycle-regulated DNA-binding protein), and is widely expressed. 155 It interacts with the first fifteen amino acids of the juxtamembrane domain of unphosphorylated ERBB3.…”
Section: Newly-identified Proteins Binding Erbb3 Phosphotyrosines-thementioning
confidence: 99%
See 1 more Smart Citation
“…33), early growth response-1 (34), and the zinc finger protein ZNF207 (34). Yoo, Zhang, and others showed that treating AU565 breast cancer cells with the ErbB-3 ligand heregulin resulted in dissociation of Ebp1 from ErbB-3 and subsequent translocation of Ebp1 to the nucleus, where it suppressed androgen receptor-mediated gene transcription (35)(36)(37). Whether Ebp1 can interact with ErbB-3 in the nucleus and whether its transcriptional activity is regulated by nuclear ErbB-3 remain to be studied.…”
Section: Discussionmentioning
confidence: 99%